Joint declaration. Organization of the black community of the Andean region - afrodescendientes de la región andina, Las organizaciones y grupos (2016)
The Afro-descendant organizations and groups of the Andean region present to the consideration of the first preparatory meeting of the World Conference of the United Nations against racial discrimination, xenophobia and other forms of intolerance.